An interventional MRI guidewire combining profile and tip conspicuity for catheterization at 0.55T. Issue 2 (5th October 2022) - Yildirim, Dursun Korel; Uzun, Dogangun; Bruce, Christopher G.; Khan, Jaffar M.; Rogers, Toby; Schenke, William H.; Ramasawmy, Rajiv; Campbell‐Washburn, Adrienne; Herzka, Daniel A.; Lederman, Robert J.; Kocaturk, Ozgur
Abstract : Purpose: We describe a clinical grade, "active", monopole antenna‐based metallic guidewire that has a continuous shaft‐to‐tip image profile, a pre‐shaped tip‐curve, standard 0.89 mm (0.035″) outer diameter, and a detachable connector for catheter exchange during cardiovascular catheterization at 0.55T. Methods: Electromagnetic simulations were performed to characterize the magnetic field around the antenna whip for continuous tip visibility. The active guidewire was manufactured using medical grade materials in an ISO Class 7 cleanroom. RF‐induced heating of the active guidewire prototype was tested in one gel phantom per ASTM 2182‐19a, alone and in tandem with clinical metal‐braided catheters. Real‐time MRI visibility was tested in one gel phantom and in‐vivo in two swine. Mechanical performance was compared with commercial equivalents. Results: The active guidewire provided continuous "profile" shaft and tip visibility in‐vitro and in‐vivo, analogous to guidewire shaft‐and‐tip profiles under X‐ray. The MRI signal signature matched simulation results. Maximum unscaled RF‐induced temperature rise was 5.2°C and 6.5°C (3.47 W/kg local background specific absorption rate), alone and in tandem with a steel‐braided catheter, respectively. Mechanical characteristics matched commercial comparator guidewires. Conclusion: The active guidewire was clearly visible via real‐time MRI at 0.55T and exhibits a favorable geometric sensitivity profile depicting the guidewire continuously from shaft‐to‐tip including a unique curved‐tip signature. RF‐induced heating is clinically acceptable. This design allows safe device navigation through luminal structures and heart chambers. The detachable connector allows delivery and exchange of cardiovascular catheters while maintaining guidewire position. This enhanced guidewire design affords the expected performance of X‐ray guidewires during human MRI catheterization.